A narrative account of the key drivers in the development of the Learning from Deaths policy. Issue 4 (October 2021) - Lalani, Mirza; Hogan, Helen
Objective: In recent years there has been a proliferation of patient safety policies in the United Kingdom triggered by well publicized failures in health care. The Learning from Deaths (LfD) policy was implemented in response to failures at Southern Health National Health Service (NHS) Foundation Trust. This study aims to develop a narrative to enable the understanding of the key drivers involved in its evolution and implications for future national patient safety policy development. Methods: A qualitative study was undertaken using documentary analysis and semi-structured interviews (n = 12) with policymakers from organizations involved in the design, implementation and assurance of LfD at a system level. Kingdon's Multiple Streams Approach was used to frame the policymaking process. Results: The publication of the Southern Health independent review and subsequent highlighting by the Care Quality Commission of a fragmented approach to learning from deaths across the NHS opened a 'policy window.' Under the influence of the families affected by patient safety failures and the then Secretary of State, acting as 'policy entrepreneurs, ' recently developed methods for mortality review were combined with mechanisms to enhance transparency and governance. This rapidly created a framework designed to ensure NHS organizations identified remedial safety problems and could be accountable for addressing them. Conclusions: The development of LfD exhibits several common features with other patient safety policies in the NHS. It was triggered by a crisis and the need for a prompt political response and attempts to address a range of concerns related to safety. In common with other safety policies, LfD contains inherent tensions related to its primary purpose, which may hinder its impact. In the absence of formal evaluations of these policies, deeper understanding of the policymaking process offers the possibility of identifying potential barriers to goal achievement.